2014
DOI: 10.3109/13651501.2014.940049
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of depression and anxiety to impaired quality of life in survivors of myocardial infarction

Abstract: Depression but not anxiety following MI predicts longer-term quality of life in myocardial infarction survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 34 publications
2
27
0
1
Order By: Relevance
“…For evidence-based correlation with other variables' validity, the Indonesian version of the MacNew questionnaire score has a negative correlation with cardiac anxiety. The result of the study was also supported by several studies (Blakemore et al, 2014;Hosseini et al, 2014;Kepka et al, 2013;Van Beek et al, 2012). The study also found that female patients' HRQOL was lower compared to male patients.…”
Section: Evidence-based On Relations With Other Variables Validitysupporting
confidence: 78%
See 2 more Smart Citations
“…For evidence-based correlation with other variables' validity, the Indonesian version of the MacNew questionnaire score has a negative correlation with cardiac anxiety. The result of the study was also supported by several studies (Blakemore et al, 2014;Hosseini et al, 2014;Kepka et al, 2013;Van Beek et al, 2012). The study also found that female patients' HRQOL was lower compared to male patients.…”
Section: Evidence-based On Relations With Other Variables Validitysupporting
confidence: 78%
“…The result of the study was supported by psychometric research conducted in Norwegian (Hiller et al, 2010). As concluded by several studies, feeling depressed and sad are the most common emotions experienced by myocardial infarction patients that correlated with HRQOL (Foxwell, Morley, & Frizelle, 2013;Hosseini et al, 2014). Item 20…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…It should be highlighted that the prognostic significance of anxiety raises discussions, since some studies suggest that post-MI anxiety symptoms were not an independent prognostic risk factor for new cardiovascular events or death. 23 Moreover, according to Hosseini et al, 24 post-MI anxiety does not predict long-term quality of life in MI survivors. Nonetheless, we believe that post-MI anxiety should be taken into consideration in clinical practice, since it has been shown that not only depression but also pre-myocardial anxiety in the preceding 2 hours increase 10-year mortality rates in those aged > 65 years.…”
Section: Discussionmentioning
confidence: 97%
“…Existing data outside of the stroke population suggest that mental health disorders have a significant impact on patient outcomes including quality of life and mortality ( 13 ). In the cardiac literature, depression has been linked to decreased quality of life, and increased all-cause mortality ( 14 17 ). Although stroke severity is a major driver of quality of life after stroke, some prior studies have shown reductions in quality of life that are out of proportion to neurologic deficits after stroke ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%